Phenotype and genotype in 101 males with X-linked creatine transporter deficiency. Issue 7 (3rd May 2013) - van de Kamp, J M; Betsalel, O T; Mercimek-Mahmutoglu, S; Abulhoul, L; Grünewald, S; Anselm, I; Azzouz, H; Bratkovic, D; de Brouwer, A; Hamel, B; Kleefstra, T; Yntema, H; et al.
Abstract : Background: Creatine transporter deficiency is a monogenic cause of X-linked intellectual disability. Since its first description in 2001 several case reports have been published but an overview of phenotype, genotype and phenotype–genotype correlation has been lacking. Methods: We performed a retrospective study of clinical, biochemical and molecular genetic data of 101 males with X-linked creatine transporter deficiency from 85 families with a pathogenic mutation in the creatine transporter gene ( SLC6A8 ). Results and conclusions: Most patients developed moderate to severe intellectual disability; mild intellectual disability was rare in adult patients. Speech language development was especially delayed but almost a third of the patients were able to speak in sentences. Besides behavioural problems and seizures, mild to moderate motor dysfunction, including extrapyramidal movement abnormalities, and gastrointestinal problems were frequent clinical features. Urinary creatine to creatinine ratio proved to be a reliable screening method besides MR spectroscopy, molecular genetic testing and creatine uptake studies, allowing definition of diagnostic guidelines. A third of patients had a de novo mutation in the SLC6A8 gene. Mothers with an affected son with a de novo mutation should be counselled about a recurrence risk in further pregnancies due to the possibility of low level somatic or germline mosaicism. Missense mutations with residual activity might be associated with a milder phenotype and large deletions extending beyond the 3′ end of the SLC6A8 gene with a more severe phenotype. Evaluation of the biochemical phenotype revealed unexpected high creatine levels in cerebrospinal fluid suggesting that the brain is able to synthesise creatine and that the cerebral creatine deficiency is caused by a defect in the reuptake of creatine within the neurones.